Shadow Banking and the Four Pillars of Traditional Financial Intermediation - Farhi, Emmanuel; Tirole, Jean (Review of Economic Studies, 2021)
Abstract Traditional banking is built on four pillars: small and medium enterprise lending, insured deposit taking, access to lender of last resort (LOLR), and prudential supervision. This article unveils the logic of the quadrilogy by showing that it emerges naturally as an equilibrium outcome in a game between banks and the government. A key insight is that regulation and public insurance services (LOLR, deposit insurance) are complementary. The model also shows how prudential regulation must adjust to the emergence of shadow banking and rationalizes structural remedies to counter bogus liquidity hoarding and financial contagion: ring-fencing between regulated and shadow banking and the sharing of liquidity in centralized platforms.